Interoperability in IoT for smart systems - Roy, Monideepa; Kar, Pushpendu; Datta, Sujoy (Boca Raton, FL : CRC Press, 2021)
"Interoperability in an IoT system is essential for going through layers of physical network, communication, and application functions. A comprehensive approach is needed to address and solve then interoperability issues of IoT devices and services from different layers. Considering these factors, proposed book discusses about different facets of interoperability issues among the IoT devices and their solutions, the scalability issues in an IoT network and provide solution for plug-n-play of new devices with the existing IoT system. It also discusses the possible usage of interoperable and plug-n-play IoT networks in different systems to make them smarter"--
Universal IoT framework / by Joy Dutta, Sarbani Roy.
OCLC-licensed vendor bibliographic record.
Keywords: Internet of things; Heterogeneous computing; Internetworking (Telecommunication); COMPUTERS / General; COMPUTERS / Networking / General; TECHNOLOGY / Electricity